1. 2x+8=3x+10
Step 1: Subtract 3x from both sides.
2x+8(-3x)= 3x+10 (-3x)
-x+8=10
Step 2: Subtract 8 from both sides.
-x+8 (-8) = 10 (-8)
-x=2
Step 3: Divide both sides by -1.
-x/(-1)=2/(-1)
x=-2
Answer= x=-2
2. -3x+9=2x-1
Step 1: Subtract 2x from each side.
-3x (-2x) +9= 2x-1 (-2x)
-5x+9=-1
Step 2: Subtract 9 from both sides.
-5x+9 (-9)=-1 (-9)
-5x=-10
Step 3: Divide -5 from both sides.
-5x/-5= -10/-5
x=2
The answer is 2.
3. 4x-7=5x-6
Step 1: Subtract 5x from both sides.
4x-7 (-5x)= 5x-6 (-5x)
-x-7=-6
Step 2: Add 7 to both sides.
-x-7 (+7)= -6 (+7)
-x=1
Step 3: Divide each side by -1.
-x/-1=1/-1
x=-1
The answer is -1.